Estimates of length-at-50% maturity of two South African demersal species: Monkfish, Lophius vomerinus, and Kingklip, Genypterus capensis - Guerra, Alessandro (Department of Biological Sciences, 2020)
Long-lived and slow-growing fish species are especially vulnerable to overfishing. Deep-sea species are elusive and difficult to study, making their management challenging. South African monkfish, Lophius vomerinus, and kingklip, Genypterus capensis, are two demersal species living off the west and south coast of South Africa. These species are exploited as bycatch in the Hake fisheries, and represent an important resource for the fishery. However, reproductive information is scarce, and key life-history parameters have not been updated in recent years. Length-at-50% maturity (L50) is a fundamental biological parameter to monitor stock-health, spawning potential and improve fishery management. This research was focused on computing L50 estimates for both species, separated by sex and coast. As the stock structure for both species is still under debate, reproductive information and L50 estimates were compared between west and south coast. In addition, L50 was compared with previous studies to detect significant differences or changes over time. Demersal survey samples were used. Individuals were classed a 5 stage maturity scale and consequently referred to as mature or immature. For L. vomerinus, a significant difference in L50 between sexes was found, in contrast with previous findings in literature. However, no significant difference between the two areas was reported, corroborating the one-stock hypothesis. Furthermore, I speculate that L. vomerinus aggregate for spawning activities. The analysis of G. capensis revealed differences between coasts, reinforcing the theory of multiple South African stocks. Most importantly, the results showed a critical reduction in females L50 from previous studies. This reduction is believed to be a consequence of excessive fishing pressure exerted particularly during the latter half of the 20th century, which overexploited immature females on the west coast and main female spawners on the south coast. Further research needs to be done to verify these findings and the stock structure of the populations.